The Greater Bay Area as a hotspot: interacting impacts of urbanization and extreme events on wet-bulb temperatures in Guangdong Province - Huang, Shitian; Su, Zhiying; Cui, Guotao; Huang, Yunling; Deng, Zixi; Lin, Shaomin (Frontiers in Climate, 2025)
Amidst rapid urbanization and an increasing frequency of extreme events, urban climate stress is intensifying and potentially affecting wet-bulb temperature (WBT), a key indicator of human-perceived thermal stress. This study examined the combined effects of urbanization and extreme events on the WBT dynamics in Guangdong Province, a humid tropical region in China. Using long-term meteorological data spanning five decades and urbanization metrics, we systematically analyzed urban–rural WBT differences using paired station comparisons and quantified the contribution of urbanization. Key findings highlight urban–rural WBT differences across three distinct urbanization stages: (a) Initial urbanization, where heat island effects dominate and amplify WBT differences; (b) Rapid urbanization, characterized by impervious surface expansion that widens WBT disparities to their peak, with the urban–rural difference increasing by 0.0027° C decade−1 (p < 0.001); and (c) Mature urbanization (e.g., Guangdong-Hong Kong-Macao Greater Bay Area, GBA), where dry island effects reduce humidity, thereby narrowing urban–rural gaps. Furthermore, extreme weather events alter these urban–rural WBT patterns. High-temperature and compound heat-drought events can reduce WBT differences, in some cases by a factor of three, while periods of extreme precipitation can amplify them. These findings underscore the critical impacts of urbanization and extreme events on urban thermal stress. This understanding is crucial for evaluating human heat stress and informing urban risk planning, particularly in the context of advancing urbanization and climate change in urban agglomerations.